ENGLISH-INDONESIAN CODE SWITCHING APPLIED IN PONDOK PESANTREN TERPADU MIFTAHUL ULUM AL-YASINI PASURUAN - Imro Atus Soliha; Ari Susandi; Benny Prasetiya (Premise: Journal of English Education and Applied Linguistics, 2020)
This article discusses Code switching of English and Arabic happens in the  Islamic boarding school: Pondok Pesantren Terpadu Miftahul Ulum Al-Yasini Pasuruan East Java. The researchers fascinated in analyzing a code-switching which usually happened at that place. The aim of this study is to find (1) the reasons in using code-switching in PPT Miftahul Ulum Al-Yasini Pasuruan, and (2) the types of code-switching used in that place by all members of the room. This is a descriptive qualitative research. In this case, interview and observation is used to get the data. This research was conducted for two weeks in the end of January 2020. The participants were  15 students from 3 rooms from Germany area which consisted for about 70 students. The results showed that the students used code-switching because of six reasons, such as: talking about specific topic, quoting somebody else, quoting someone else, interjection, recurrence for clarification, clarification the speech content for the interlocutor, to strengthen or soften some requests and command, and because of lexical need. The implication is that code-switching is inevitable due to various situation. It occurs in the context of EFL particularly when two foreign languages are simultaneously learned.  Keywords: bilingualism, code switching, Pesantren, sociolinguistics.